The value-adoption problem in the Malaysian Islamic banking system - Imon, Riasat Amin (2019)
Despite being the largest arm of the Malaysian Islamic financial sector, the Malaysian Islamic banking system has always been an active target of critics for the lack of structural reforms to fortify core Islamic values, such as, risk-sharing and real sector growth. Often, the blame is thickly laid on strategic management entities, such as the executive management and the Shariah committee. This paper presents the structural-development-problem of Islamic banks as a systemic problem that results from an inevitable value-adoption process effected by the mainstream financial systems it emulates. Thus, the development of Islamic banking is contingent upon the value-framework within which it has been set. This would explain why Islamic banking has unfalteringly developed according to mainstream financial standards while resisting structural change. The implication is that for meaningful development to occur in this sector, the choice of more compatible value-laden frameworks is critical.